Розкладання пероксидних сполук вуглецевими нанотрубками: параметри, що визначають активність каталізатора - Voitko, K. V.; Bakalinska, O. M.; Kartel, M. T. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2019)
The catalytic system “carbon nanotubes/peroxide molecule” in aqueous/non-aqueous media was investigated for determining of the main factors that influence on catalyst’s effectiveness. The catalytic activity of as-synthesized multi-walled carbon nanotubes, and their modified forms (oxidized and nitrogen doped) were investigated in the decomposition of hydrogen, benzoyl (BP) and lauroyl (LP) peroxides at room temperature by measuring the volume of released gases. Ethyl acetate and tetrachloromethane were used for BP and LP decomposition respectively. Among factors that determined the catalytic performance of investigated samples their structural-sorption properties, surface chemistry and diffusion limitation have been considered. It was established that CNT show moderate activity in aqueous medium because of internal diffusion limitation. As a consequence, their performance is determined by the textural characteristic of carbon matrices. Based on the calculated diffusion coefficients it was concluded that catalysis by CNT in non-aqueous area is carried out in the kinetic region on their accessible surface. Such catalytically active surface has a lot of N-containing functional groups as well as basic O-containing ones, therefore it shows better activity towards organic peroxides. Moreover, CNT’s surface is more hydrophobic that is promoting the reaction proceeding in non-aqueous media. The decomposition rate of steric BP is lower compared to the long chain of LP. Based on this finding, it could be predicted that mesoporous CNT with high content basic functionalities and good surface accessibility should be the excellent catalyst for diacyl peroxides decomposition in organic solvents.